Safety and efficacy of nivolumab in combination with S-1/capecitabine plus oxaliplatin in patients with previously untreated, unresectable, advanced, or recurrent gastric/gastroesophageal junction cancer: interim results of a randomized, phase II trial (ATTRACTION-4). (19th December 2018) - Boku, N; Ryu, M -H; Kato, K; Chung, H C; Minashi, K; Lee, K -W; Cho, H; Kang, W K; Komatsu, Y; Tsuda, M; Yamaguchi, K; Hara, H; et al.
Abstract: Background: Nivolumab is approved as an option for third- or later-line treatment of advanced gastric/gastroesophageal junction (G/GEJ) cancer in several countries after ATTRACTION-2. To further improve the therapeutic efficacy of first-line therapy, exploration of a nivolumab-chemotherapy combination is warranted. In part 1 (phase II) of ATTRACTION-4, the safety and efficacy of nivolumab combined with S-1 plus oxaliplatin (SOX) or capecitabine plus oxaliplatin (CapeOX) as first-line therapy for unresectable advanced or recurrent human epidermal growth factor receptor 2 (HER2)-negative G/GEJ cancer were evaluated. Patients and methods: Patients were randomized (1 : 1) to receive nivolumab (360 mg intravenously every 3 weeks) plus SOX (S-1, 40 mg/m 2 orally twice daily for 14 days followed by 7 days off; oxaliplatin, 130 mg/m 2 intravenously on day 1 every 3 weeks) or CapeOX (capecitabine, 1000 mg/m 2 orally twice daily for 14 days followed by 7 days off; oxaliplatin, 130 mg/m 2 intravenously on day 1 every 3 weeks) until disease progression, unacceptable toxicity, or consent withdrawal. Results: Of 40 randomized patients, 39 (nivolumab plus SOX, 21; nivolumab plus CapeOX, 18) and 38 (21 and 17, respectively) comprised the safety and efficacy populations, respectively. Most frequent (>10%) grade 3/4 treatment-related adverse events were neutropenia (14.3%) in the nivolumab plus SOX group, and neutropenia (16.7%), anemia, peripheral sensory neuropathy, decreased appetite, type 1 diabetes mellitus, and nausea (11.1% each) in the nivolumab plus CapeOX group. No treatment-related death occurred. Objective response rate was 57.1% (95% confidence interval 34.0–78.2) with nivolumab plus SOX and 76.5% (50.1–93.2) with nivolumab plus CapeOX. Median overall survival was not reached (NR) in both groups. Median progression-free survival was 9.7 months (5.8–NR) and 10.6 months (5.6–12.5), respectively. Conclusion: Nivolumab combined with SOX/CapeOX was well tolerated and demonstrated encouraging efficacy for unresectable advanced or recurrent HER2-negative G/GEJ cancer. ATTRACTION-4 has proceeded to part 2 (phase III) to compare nivolumab plus SOX/CapeOX versus placebo plus SOX/CapeOX. Clinicaltrials.gov ID: NCT02746796.